2009
DOI: 10.1016/j.fuel.2009.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Fast pyrolysis of heavy metal contaminated willow: Influence of the plant part

Abstract: a b s t r a c tFast pyrolysis of heavy metal contaminated willow, with high concentrations of Cd, Cu, Pb and Zn, resulting from phytoremediation, is investigated. The distribution of the heavy metals depends on the plant part (leaves and branches). Nevertheless, their individual pyrolysis fractions (at an operational temperature of 623 K), i.e., bio-oil/tar and gas, are both heavy metal free. Some small differences in the kind and amounts of the organic compounds are found in the bio-oil and gaseous fraction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 16 publications
2
52
0
Order By: Relevance
“…experiment. Therefore, reactor type, pyrolysis conditions and experimental scale are different from previous research [6][7][8][9]. Crops subjected to pyrolysis are poplar (populus Deltoides  populus Trichocampa), and two willow cultivars (salix Fragilis ''Belgian red'' and salix Jorunn).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…experiment. Therefore, reactor type, pyrolysis conditions and experimental scale are different from previous research [6][7][8][9]. Crops subjected to pyrolysis are poplar (populus Deltoides  populus Trichocampa), and two willow cultivars (salix Fragilis ''Belgian red'' and salix Jorunn).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of 3 g biomass per batch is pyrolysed in a quartz tubular reactor heated at 30 K/min [6,7]. It has been found that both condensable and non-condensable pyrolysis (623 K) fractions of both contaminated willows stems and leaves contain no detectable amounts of Cd, Cu and Pb while very small amounts of Zn (<5 ppm) are found in the condensable pyrolysis fraction (623 K) [8]. Pilot scale pyrolysis of synthetic hyperaccumulator biomass is demonstrated as well [9].…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive literature on pyrolysis of biomass (Seon et al, 2010;Hyeon et al, 2010;Liu et al, 2010;Bridgwater, 1999;Putun et al, 2008;Charles et al, 2008;Lievens et al, 2009;Smith et al, 2009;Oasmaa et al, 2005). In the above studies, bio-oils were obtained by decomposing biomass samples at different pyrolysis conditions and characteristics of the obtained bio-oil were also investigated by various instrumental techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature is focused on three goals: (1) to prevent heavy metals from being released into the environment; (2) to produce valuable pyrolysis oil that is free of heavy metals; and (3) to accumulate the heavy metals in the char/ash residue (hereafter described as 'char') (Lievens et al 2009;Stals et al 2010;Han et al 2013;Cheng 2014;Yang et al 2014). It has been found that both condensable and non-condensable pyrolysis (623 K) fractions of both contaminated willow stems and leaves contain no detectable amounts of Cd, Cu or Pb but very small amounts of Zn (\5 ppm) are found in the condensable pyrolysis fraction (623 K) (Lievens et al 2009). Pilot scale pyrolysis of synthetic hyperaccumulator biomass has also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…biooil/tar and gas, were both free of heavy metals. Some small differences in the types and amounts of organic compounds are found in the bio-oil and gaseous fractions (Lievens et al 2009). Another approach for processing of phytoremediation crops is based on conversion into bioenergy using different energy-recovery techniques (Keller et al 2005).…”
Section: Introductionmentioning
confidence: 99%